Análisis financiero a los balances de almacén motocross de la ciudad de Gualaquiza, provincia de Morona Santiago, periodo 2014 - 2015. - Wampash Antuash, Eudosia Bibiana (2018)
The present investigation determined the true financial structure of the Warehouse, facilitating the owner to apply corrective measures for the benefit of the organization, it was also developed with the purpose of fulfilling a prerequisite to choose the degree in Accounting and Audit Engineering, title that grants the National University of Loja, Career of Accounting and Audit. In order to comply with the proposed objectives, the Vertical, Horizontal Financial Analysis and execution of the respective Indicators was applied, the same that helped me determine the possible risks, to know the level of indebtedness of the organization, it served me as a necessary tool according to the activities carried out, in the same way a Financial Analysis report was prepared that is addressed to the Owner, which will be of valuable help in decision making. It has its own and sufficient capital; the liquidity of the company is favorable because its Current Assets are superior to Current Liabilities, it keeps the products stored due to the low turnover of inventories, reason in which they do not generate profits, caution must be exercised in the financial management of their resources; the Accounts Receivable and Inventory must be analyzed in order to recover the investments made in the shortest time. Additionally, we propose the respective conclusions and recommendations that will help to give possible solutions to the problems found in the company, among the most important we have never made a Financial Analysis so the owner is recommended to do it annually or at least less every two years for making appropriate decisions.